2020
DOI: 10.33403/rigeo.677322
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on the Urban Perception of Disabled Students in Samsun (Turkey)

Abstract: Individual differences, especially physical disabilities, play a significant role in people's perception of their living places and their attitudes in these environments. Accordingly, the starting point of the present research is based on the possible contributions and developments of the implementations and studies partly eliminating the negative aspects of individual disabilities to the perceptions and information of the disabled people regarding the physical and social environment that they live in. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…For example, C. Didelon-Loiseau et al utilized mental maps to identify the regional perception of the whole world by respondents from different countries [1]. In contrast to this, S. Gül used mental maps as a basis to study the urban perception of students at the city level [8]. K. Hátlová et al found out that mental maps are most of all influenced by biological, psychological, sociocultural, environmental, and educational factors [6].…”
Section: Related Workmentioning
confidence: 99%
“…For example, C. Didelon-Loiseau et al utilized mental maps to identify the regional perception of the whole world by respondents from different countries [1]. In contrast to this, S. Gül used mental maps as a basis to study the urban perception of students at the city level [8]. K. Hátlová et al found out that mental maps are most of all influenced by biological, psychological, sociocultural, environmental, and educational factors [6].…”
Section: Related Workmentioning
confidence: 99%